Conductive paste, preparation method thereof and radio frequency identification tag

By optimizing the conductive paste components and surface modification treatment, the contradiction between the conductivity, fluidity and flexibility of traditional conductive paste is resolved, efficient conductive performance and good printability are achieved, and the signal transmission efficiency and stability of radio frequency identification tags are improved.

CN120727338APending Publication Date: 2025-09-30ZHEJIANG KING LABLE TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510755352.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-06
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

Traditional conductive pastes have a contradiction between their conductive properties and processing fluidity and flexibility, resulting in uneven coating thickness and easy breakage of the antenna structure during the printing process, affecting the signal transmission efficiency and stability of the RFID tag.

Method used

The synergistic effect of high-sphericity silver powder and carbon nanotubes, combined with surface modification treatment, is used to prepare a resin binder through a hydrosilylation reaction to form a continuous conductive network and optimize the fluidity and flexibility of the slurry.

Benefits of technology

It significantly improves the fluidity and conductive efficiency of the conductive paste, improves printability, ensures the integrity of the antenna structure during bending, and increases the reading distance and stability of the RFID tag.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses conductive paste, a preparation method thereof and a radio frequency identification tag. The conductive paste comprises the following raw materials in parts by mass: 30-40 parts of spherical silver powder, 3-6 parts of carbon nanotubes, 20-30 parts of a resin adhesive, 40-50 parts of a diluent and 2-4 parts of a dispersant, the resin adhesive comprises polyurethane resin and an organosilicone modified acrylate monomer in a mass ratio of (8-9): (1-2), and the organosilicone modified acrylate monomer is obtained by hydrosilylation of a hydroxyl acrylate monomer and a hydrogen-containing silane compound in a molar ratio of (1.0-1.1): 1. According to the invention, the contradiction between the conductive performance and fluidity and the product flexibility of the conductive paste can be effectively solved, and the RFID product with high conductivity, printing quality and mechanical flexibility can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of conductive paste, and in particular to a conductive paste, a preparation method thereof, and a radio frequency identification tag. Background Art

[0002] Radio Frequency Identification (RFID) technology is a core component of the Internet of Things (IoT). The performance of its tag antennas directly impacts signal transmission efficiency and identification reliability. Traditional RFID tag antennas are typically produced using a printing process using conductive paste. The performance of the conductive paste is a key factor in determining the antenna's conductivity and structural integrity.

[0003] Currently, conductive pastes primarily enhance their conductivity by adding a high proportion of conductive powders (such as silver powder, copper powder, or graphene). However, the high addition of these conductive powders often leads to a significant increase in paste viscosity and a decrease in fluidity. During the printing process, pastes with excessively high viscosity make it difficult to evenly fill the fine structures of the template or screen, leading to localized leaks or uneven coating thickness, which in turn can cause breakpoints or discontinuities in the antenna line. These structural defects not only weaken the antenna's conductivity but can also cause impedance mismatch during high-frequency signal transmission, reducing the read range and stability of RFID tags. Furthermore, excessive addition of conductive powders significantly reduces the flexibility of the cured coating. Antenna structures formed with conventional conductive pastes are prone to cracking or even breaking when bent, resulting in a loss of conductivity. Summary of the Invention

[0004] In order to resolve the contradiction between the conductive performance of a conductive paste and its processing fluidity and product ductility, the present application provides a conductive paste, a preparation method thereof, and a radio frequency identification tag.

[0005] In a first aspect, the present application provides a conductive paste comprising the following raw materials in parts by weight: 30-40 parts of spherical silver powder, 3-6 parts of carbon nanotubes, 20-30 parts of resin binder, 40-50 parts of diluent, and 2-4 parts of dispersant; The resin adhesive comprises a polyurethane resin and an organosilicon-modified acrylate monomer in a mass ratio of 8-9:1-2. The organosilicon-modified acrylate monomer is obtained by a hydrosilylation reaction of a hydroxy acrylate monomer and a hydrogen-containing silane compound in a molar ratio of 1.0-1.1:1.

[0006] In any of the above technical solutions, the hydrogen-containing silane compound is one or more of trimethoxysilane, triethoxysilane, triisopropoxysilane, methyldimethoxysilane, ethyldimethoxysilane, and methyldiethoxysilane.

[0007] In any of the above technical solutions, the hydrosilylation reaction is carried out in the presence of a platinum catalyst, with the amount of platinum catalyst used being 20 to 40 ppm (in terms of Pt) based on the total mass of the reactants.

[0008] In any of the above technical solutions, the hydroxy acrylate monomer is one or more of trimethylolpropane diacrylate, pentaerythritol triacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, and hydroxybutyl acrylate.

[0009] In any of the above technical solutions, the sphericity of the spherical silver powder is not less than 0.8.

[0010] In any of the above technical solutions, the particle size of the spherical silver powder is 1 to 15 μm.

[0011] The sphericity refers to the ratio of the maximum diameter of the projected outline of the silver powder particles to the minimum diameter of the circle that can contain the projected outline of the silver powder. The closer the sphericity value is to 1, the closer the shape of the filler particles is to a sphere.

[0012] This application effectively solves the difficult problem of balancing conductivity, printability and flexibility in traditional conductive pastes by optimizing the components of the conductive paste. First, the use of highly spherical silver powder as the main conductive filler can significantly reduce the frictional resistance between particles, improve the fluidity of the paste, and avoid leakage or uneven coating thickness caused by excessive viscosity during the printing process. On the other hand, the introduction of carbon nanotubes, through their unique tubular structure and ultra-high aspect ratio, plays a "bridging" role in the conductive network, filling the gaps between silver powder particles to form a continuous three-dimensional conductive path, thereby improving the overall conductivity of the paste.

[0013] In the resin adhesive design, a two-component polyurethane resin and a silicone-modified acrylate monomer have a synergistic effect. Specifically, the silicone-modified acrylate monomer is prepared by the hydrosilylation reaction of hydroxy acrylate and hydrosilane. The hydroxyl groups in its molecular chain can react with the -NCO groups of the polyurethane, ensuring the efficient curing process. The introduced silicone segments give the cured conductive antenna structure excellent flexibility, maintaining structural integrity even under repeated bending. In addition, the low surface energy characteristics of the silicone segments can also reduce the viscosity of the slurry, further improving printability, forming a comprehensive performance advantage of high conductivity, good processing fluidity, and mechanical flexibility.

[0014] In any of the above technical solutions, 2-mercaptoimidazole is grafted onto the surface of the spherical silver powder, and the mass ratio of the spherical silver powder to 2-mercaptoimidazole is 100:3-6.

[0015] In any of the above technical solutions, the surface of the carbon nanotubes is grafted with an alkylsiloxane compound and a metal phthalocyanine complex, and the mass ratio of the carbon nanotubes, the alkylsiloxane compound and the metal phthalocyanine complex is 100:5-10:10-15.

[0016] In any of the above technical solutions, the metal phthalocyanine complex is copper phthalocyanine and / or zinc phthalocyanine.

[0017] In any of the above technical solutions, the alkylsiloxane compound is a C8-C16 siloxane compound.

[0018] Exemplarily, the C8 siloxane compound is octyltrimethoxysilane or octyltriethoxysilane.

[0019] Exemplarily, the C12 siloxane compound is dodecyltrimethoxysilane or dodecyltriethoxysilane.

[0020] This application effectively solves the problem of dispersing conductive powders in high-fluidity slurry systems through multi-stage surface modification. For silver powder, the 2-mercaptoimidazole grafted on its surface forms a stable chemical adsorption layer through the strong coordination between the mercapto group and the silver atoms. At the same time, the steric hindrance effect of the imidazole group can significantly inhibit the van der Waals force aggregation between the silver powder particles, preventing sedimentation. For carbon nanotubes, on the one hand, long-chain alkylsiloxane groups are used as modifiers. Their alkyl chains hinder the stacking and aggregation of carbon nanotubes through the steric hindrance effect; on the other hand, the phthalocyanine molecules are anchored to the surface of the carbon nanotubes through the strong interaction between the metal phthalocyanine complex and the π electron cloud on the surface of the carbon nanotubes. The metal center in the phthalocyanine complex can also form a coordination bond with the imidazole group on the surface of the silver powder, thereby constructing a "chemical bridge" between the silver powder and the carbon nanotubes, reducing the interfacial contact resistance and promoting electron transfer. This synergistic effect not only inhibits the agglomeration of the conductive powder, but also optimizes the conductive network through interfacial chemical bonding, significantly improving the conductive efficiency and long-term stability of the slurry.

[0021] It should be noted that if the alkyl chain of an alkylsiloxane is too short (less than C8), its steric hindrance is insufficient, making it difficult to effectively inhibit the π-π stacking and aggregation of carbon nanotubes, resulting in a decrease in dispersibility. If the alkyl chain is too long (more than C16), although the steric hindrance is enhanced, the excessively long hydrophobic chain segment may hinder the interfacial contact between the carbon nanotubes and the resin or conductive filler, increasing the electron transport resistance and reducing the conductivity efficiency. The chain length of C8 to C16 can provide a moderate steric effect to ensure dispersion stability while avoiding the increase in interfacial impedance caused by excessively long chain segments, achieving a synergistic optimization of dispersibility and conductivity.

[0022] In a second aspect, the present application provides a method for preparing a conductive paste, which is prepared by mixing raw materials according to any of the above conductive pastes.

[0023] In a third aspect, the present application provides a radio frequency identification tag, which includes an antenna structure, and the antenna structure is printed using any of the above-mentioned conductive pastes.

[0024] In any of the above technical solutions, the radio frequency identification tag includes a substrate and an antenna structure printed on the substrate, and the chip is coupled to the antenna by a flip-chip bonding method.

[0025] In summary, this application has the following beneficial effects: This application prepares a conductive paste with high conductivity, excellent printability and good flexibility through component optimization and interface modification. A low-defect continuous conductive network is constructed by the synergistic effect of high-sphericity silver powder and carbon nanotubes. Combined with the dispersing and stabilizing function of mercaptoimidazole on the surface of the silver powder, the fluidity and conductive efficiency of the paste are significantly improved. The compounding of two-component polyurethane and silicone-modified acrylate monomer in the resin adhesive enhances the flexibility of the antenna structure by introducing silicone segments while ensuring the activity of the curing reaction. The alkylsiloxane and metal phthalocyanine complexes grafted on the surface of the carbon nanotubes further optimize the dispersibility and reduce the transmission barrier through interfacial coordination bonds. A balance between conductivity, processing performance and mechanical flexibility is achieved. DETAILED DESCRIPTION Preparation Example

[0026] Preparation Example 1-1, organosilicon-modified acrylate monomer, was prepared as follows: Under nitrogen, 1.05 mol of hydroxyethyl acrylate and 1 mol of trimethoxysilane were added to a reactor and stirred evenly. Castaplatin catalyst (30 ppm, calculated as Pt) was added, the temperature was raised to 75°C, and the reaction was stirred continuously for 5 hours. After the reaction was completed, the temperature was raised to 105°C and vacuum distillation (-0.09 MPa) was performed for 0.5 h to remove low-molecular impurities, thereby obtaining the organosilicon-modified acrylate monomer.

[0027] Preparation Example 1-2, organosilicon-modified acrylate monomer, was prepared as follows: Under nitrogen, 1.0 mol of pentaerythritol triacrylate and 1 mol of methyldimethoxysilane were added to a reactor and stirred thoroughly. Castaplatin catalyst (20 ppm, calculated as Pt) was added, and the temperature was raised to 75°C. Stirring was continued for 6 hours. After the reaction, the temperature was raised to 120°C and the mixture was distilled under reduced pressure (-0.1 MPa) for 1 hour to remove low-molecular impurities, thereby obtaining the organosilicon-modified acrylate monomer.

[0028] Preparation Example 1-3, organosilicon-modified acrylate monomer, was prepared as follows: Under nitrogen, 1.1 mol of hydroxypropyl methacrylate and 1.0 mol of ethyldimethoxysilane were added to a reactor and stirred evenly. Castaplatin catalyst (40 ppm, calculated as Pt) was added, the temperature was raised to 70°C, and the reaction was stirred continuously for 5 hours. After the reaction was completed, the temperature was raised to 100°C and vacuum distilled (-0.09 MPa) for 0.5 h to remove low-molecular impurities, thereby obtaining the silicone-modified acrylate monomer.

[0029] Preparation Example 2-1: A modified spherical silver powder was prepared as follows: 100g of spherical silver powder (sphericity 0.9±0.05, particle size 5-10µm) was dispersed in 400mL of anhydrous ethanol and sonicated for 30 minutes to form a homogeneous suspension. 4.5g of 2-mercaptoimidazole was added and stirred at room temperature for 8 hours. The mixture was centrifuged, washed three times with ethanol to remove unreacted 2-mercaptoimidazole, and vacuum dried at 60°C for 6 hours to obtain modified spherical silver powder with 2-mercaptoimidazole grafted on its surface.

[0030] Preparation Example 2-2, a modified spherical silver powder was prepared by the following operation: 100g of spherical silver powder (sphericity 0.85±0.05, particle size 5-10µm) was dispersed in 400mL of anhydrous ethanol and sonicated for 30 minutes to form a homogeneous suspension. 3g of 2-mercaptoimidazole was added and the suspension was stirred at room temperature for 6 hours. The suspension was centrifuged, washed three times with ethanol to remove unreacted 2-mercaptoimidazole, and vacuum dried at 50°C for 8 hours to obtain surface-modified spherical silver powder grafted with 2-mercaptoimidazole.

[0031] Preparation Example 2-3, a modified spherical silver powder was prepared by the following operation: 100 g of spherical silver powder (sphericity 0.9 ± 0.05, particle size 8–12 µm) was dispersed in 400 mL of anhydrous ethanol and sonicated for 30 minutes to form a homogeneous suspension. 6 g of 2-mercaptoimidazole was added and the suspension was stirred at room temperature for 10 hours. The suspension was centrifuged, washed three times with ethanol to remove unreacted 2-mercaptoimidazole, and vacuum dried at 60°C for 6 hours to obtain surface-grafted 2-mercaptoimidazole-modified spherical silver powder.

[0032] Preparation Example 2-4, a modified spherical silver powder was prepared by the following operation: 100 g of spherical silver powder (sphericity 0.9 ± 0.05, particle size 8–12 µm) was dispersed in 400 mL of anhydrous ethanol and sonicated for 30 minutes to form a homogeneous suspension. 6 g of dodecyltrimethoxysilane was added and stirred at room temperature for 2 hours. The mixture was centrifuged, washed three times with ethanol to remove unreacted dodecyltrimethoxysilane, and vacuum dried at 60°C for 6 hours to obtain surface-modified spherical silver powder grafted with dodecyltrimethoxysilane.

[0033] Preparation Example 3-1: A modified carbon nanotube was prepared by the following operation: 100g of multi-walled carbon nanotubes (average diameter 10-30nm, aspect ratio >500) were dispersed in dimethylformamide (5 wt%) and sonicated for 1 hour. 12.5g of copper phthalocyanine was added and stirred at 80°C for 3 hours. The mixture was centrifuged, washed three times with dimethylformamide, and dried to obtain an intermediate.

[0034] The intermediate was dispersed in toluene, and 7.5 g of octyltrimethoxysilane was added. The mixture was stirred at 70° C. for 2 hours, centrifuged, washed twice with toluene, and dried in vacuo.

[0035] Preparation Example 3-2: A modified carbon nanotube was prepared as follows: 100g of multi-walled carbon nanotubes (average diameter 10-30nm, aspect ratio >500) were dispersed in dimethylformamide (5 wt%) and sonicated for 1 hour. 10g of zinc phthalocyanine was added and stirred at 80°C for 2 hours. The mixture was centrifuged, washed three times with dimethylformamide, and dried to obtain an intermediate.

[0036] The intermediate was dispersed in toluene, and 10 g of dodecyltriethoxysilane was added. The mixture was stirred at 60° C. for 3 hours, centrifuged, washed twice with toluene, and dried in vacuo to obtain the product.

[0037] Preparation Example 3-3: A modified carbon nanotube was prepared by the following operation: 100g of multi-walled carbon nanotubes (average diameter 10-30nm, aspect ratio >500) were dispersed in dimethylformamide (5 wt%) and sonicated for 1 hour. 15g of copper phthalocyanine was added and stirred at 80°C for 4 hours. The mixture was centrifuged, washed three times with dimethylformamide, and dried to obtain an intermediate.

[0038] The intermediate was dispersed in toluene, 5 g of hexadecyltrimethoxysilane was added, stirred at 70° C. for 2 hours, centrifuged, washed twice with toluene, and dried in vacuum to obtain the product.

[0039] Preparation Example 3-4, a modified carbon nanotube, differs from Preparation Example 3-1 in that octyltrimethoxysilane is replaced by an equal mass of hexyltrimethoxysilane.

[0040] Preparation Example 3-5, a modified carbon nanotube, differs from Preparation Example 3-1 in that octyltrimethoxysilane is replaced by an equal mass of octadecyltrimethoxysilane.

[0041] Preparation Example 3-6, a modified carbon nanotube, differs from Preparation Example 3-1 in that octyltrimethoxysilane is replaced by an equal mass of copper phthalocyanine.

[0042] Preparation Example 3-7, a modified carbon nanotube, differs from Preparation Example 3-1 in that copper phthalocyanine is replaced by an equal mass of octyltrimethoxysilane. Example

[0043] Example 1: A conductive paste is prepared according to the following steps: Mix 212.5g of polyurethane resin (5836P), 37.5g of the silicone-modified acrylate monomer from Preparation Example 1-1, and 450g of terpineol and stir at 50°C until homogeneous and transparent. Then, add 350g of the modified spherical silver powder from Preparation Example 2-1 and 45g of the modified carbon nanotubes from Preparation Example 3-1. Mechanically stir at 500rpm for 30 minutes to obtain a mixture. Transfer the mixture to a three-roll mill (roller gap 10µm) and grind three times to a slurry fineness of ≤5µm. Add 30g of BYK-111 dispersant and ultrasonically disperse (40kHz) for 30 minutes to remove bubbles.

[0044] Example 2: A conductive paste is prepared according to the following steps: Mix 198g of polyurethane resin (5836P), 22g of the silicone-modified acrylate monomer from Preparation Example 1-2, and 500g of diethylene glycol butyl ether and stir at 60°C until homogeneous and transparent. Then, add 320g of the modified spherical silver powder from Preparation Example 2-2 and 35g of the modified carbon nanotubes from Preparation Example 3-2. Mechanically stir at 500rpm for 30 minutes to obtain a mixture. Transfer the mixture to a three-roll mill (roller gap 10µm) and grind three times to a slurry fineness of ≤5µm. Add 20g of BYK-161 dispersant and ultrasonically disperse (40kHz) for 30 minutes to remove bubbles.

[0045] Example 3, a conductive paste is prepared according to the following steps: Mix 240g of polyurethane resin (5836P), 60g of the silicone-modified acrylate monomer from Preparation Example 1-3, and 480g of terpineol. Stir in a 50°C water bath until homogeneous and transparent. Add 390g of the modified spherical silver powder from Preparation Example 2-3 and 55g of the modified carbon nanotubes from Preparation Example 3-3 in sequence. Mechanically stir at 500rpm for 30 minutes to obtain a mixture. Transfer the mixture to a three-roll mill (roller gap 10µm) and grind three times to a slurry fineness of ≤5µm. Add 40g of BYK-111 dispersant and ultrasonically disperse (40kHz) for 30 minutes to remove bubbles.

[0046] Example 4 is a conductive paste. The difference from Example 1 is that the modified carbon nanotubes of Preparation Example 3-1 are replaced by the modified carbon nanotubes of Preparation Example 3-4 of equal mass.

[0047] Example 5 is a conductive paste. The difference from Example 1 is that the modified carbon nanotubes of Preparation Example 3-1 are replaced by the modified carbon nanotubes of Preparation Example 3-5 of equal mass.

[0048] Example 6 is a conductive paste. The difference from Example 1 is that the modified carbon nanotubes of Preparation Example 3-1 are replaced by the modified carbon nanotubes of Preparation Example 3-6 of equal mass.

[0049] Example 7, a conductive paste, differs from Example 1 in that the modified carbon nanotubes of Preparation Example 3-1 are replaced by the modified carbon nanotubes of Preparation Example 3-7 of equal mass.

[0050] Example 8, a conductive paste, differs from Example 1 in that the modified spherical silver powder of Preparation Example 2-1 is replaced by the modified spherical silver powder of Preparation Example 2-4 of equal mass.

[0051] Example 9, a conductive paste, differs from Example 7 in that the modified spherical silver powder of Preparation Example 2-4 is used in place of the modified spherical silver powder of Preparation Example 2-1 with an equal mass. Comparative Example

[0052] Comparative Example 1 is a conductive paste, which differs from Example 9 in that the silicone-modified acrylate monomer of Preparation Example 1-1 is replaced by an equal mass of polyurethane resin (5836P).

[0053] Comparative Example 2 is a conductive paste, which differs from Example 9 in that the organosilicon-modified acrylate monomer in Preparation Example 1-1 is replaced by an equal amount of hydroxyethyl acrylate. Performance testing

[0054] Test 1: Conductivity test Test method: Print the conductive paste on coated paper to obtain a sample with a size of 1cm×1cm. Dry the sample after printing. Use a four-probe square resistance meter (DWR1C) to measure the square resistance of the sample. Place the four probes on the diagonal of the sample and read the square resistance value. Use a film thickness meter to measure the thickness of the printed film and convert the square resistance into conductivity. Record the average value of 5 measurements: Conductivity = 1 / (sheet resistance × film thickness).

[0055] Test 2: Flexibility test Test method: Use a dynamic bending tester (radius 3 mm, frequency 1 Hz) to bend the material 1000 times. Then measure the conductivity according to the method in Test 1. Calculate the conductivity retention (%).

[0056] Retention rate = conductivity after bending / initial conductivity × 100 Test 3: Paste printing performance test Test method: Use a 200-mesh screen to print the antenna pattern (line width 0.2mm, spacing 0.3mm) at a printing speed of 10mm / s. Observe the continuity of the printed circuit using an optical microscope (50×), and count the number of missing materials or breakpoints per 10cm of line length.

[0057] Test 4: Slurry dispersion test Test method: Pour the conductive slurry into a transparent glass tube (2 cm in diameter, 20 cm in height), seal it and let it stand; record the layer height (the interface between the upper clear liquid and the lower sediment) after the slurry is left at 25°C for 14 days. Calculate the sedimentation rate: Sedimentation rate = sedimentation layer height / initial slurry height × 100% Table 1. Performance test results

[0058] Analysis of test results: After 1000 repeated bends, the conductivity retention of the printed antennas of Examples 1-9 was significantly higher than that of Comparative Examples 1-2, indicating that the flexibility of the examples was better than that of the comparative examples, indicating that the introduction of the organosilicon segments effectively improved the flexibility of the drop-in printing structure.

[0059] The electrical conductivity of Example 1 is significantly higher than that of Example 7 (ungrafted copper phthalocyanine), Example 8 (ungrafted mercaptoimidazole), and Example 9 (ungrafted copper phthalocyanine and mercaptoimidazole), and the electrical conductivities of Examples 7-9 are close, verifying the synergistic effect of copper phthalocyanine and mercaptoimidazole, which reduces the interfacial resistance between carbon nanotubes and silver powder through coordination bonding, thereby improving the conductive properties of the slurry.

[0060] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A conductive paste, characterized in that: Including the following raw materials by weight: 30-40 parts of spherical silver powder, 3-6 parts of carbon nanotubes, 20-30 parts of resin binder, 40-50 parts of diluent, and 2-4 parts of dispersant; The resin adhesive comprises a polyurethane resin and an organosilicon-modified acrylate monomer in a mass ratio of 8-9:1-2. The organosilicon-modified acrylate monomer is obtained by a hydrosilylation reaction of a hydroxy acrylate monomer and a hydrogen-containing silane compound in a molar ratio of 1.0-1.1:

1.

2. The conductive paste according to claim 1, characterized in that The hydrogen-containing silane compound is one or more of trimethoxysilane, triethoxysilane, triisopropoxysilane, methyldimethoxysilane, ethyldimethoxysilane, and methyldiethoxysilane.

3. The conductive paste according to claim 1, characterized in that The hydroxy acrylate monomer is one or more of trimethylolpropane diacrylate, pentaerythritol triacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, and hydroxybutyl acrylate.

4. The conductive paste according to claim 1, characterized in that The sphericity of the spherical silver powder is not less than 0.

8.

5. The conductive paste according to claim 1, characterized in that 2-mercaptoimidazole is grafted on the surface of the spherical silver powder, and the mass ratio of the spherical silver powder to the 2-mercaptoimidazole is 100:3-6.

6. The conductive paste according to claim 5, characterized in that Alkylsiloxane compounds and metal phthalocyanine complexes are grafted onto the surface of the carbon nanotubes. The mass ratio of the carbon nanotubes, the alkylsiloxane compounds and the metal phthalocyanine complexes is 100:5-10:10-15.

7. The conductive paste according to claim 6, characterized in that: The metal phthalocyanine complex is copper phthalocyanine and / or zinc phthalocyanine.

8. The conductive paste according to claim 6, characterized in that: The alkylsiloxane compound is a C8-C16 siloxane compound.

9. A method for preparing a conductive paste, characterized in that: The slurry is prepared by mixing the raw materials according to any one of claims 1 to 8.

10. A radio frequency identification tag, characterized in that: The invention comprises an antenna structure, wherein the antenna structure is obtained by printing the conductive paste according to any one of claims 1 to 8.

Citation Information

Cited By

  • Low-temperature anti-oxidation conductive copper paste, preparation method and RFID tag

    CN121306628A

  • Low-temperature antioxidant conductive copper paste, preparation method and RFID tag

    CN121306628B